Treating Centric Systematic Sample as a Random Sample - Morashi, V. K. (Indian Forester, 1968)
The author has attempted to experimentally verify the findings of Milne (1959) in connection with the risk involved in treating centric systematic sample as a random sample. His findings support the conclusions of Milne that there is no risk in treating centric systematic sample as a random sample. The general applicability of these findings is not dealt with in the paper as the same has been done in great details by Milne.